KATEGORI FATIS DALAM KOMENTAR DI AKUN MEDIA SOSIAL PARTAI GERINDRA - Herlita Sari Br Pinem; Dairi Sapta Rindu Simanjuntak; Klarentina Ria Sinaga; Yulica Sari Fransisca Purba; Amelia Sembiring; Putri Audy Harianja (Jurnal Bastra (Bahasa dan Sastra), 2025)
Language has several functions, one of which is the vocal function. Phonetic phrases or utterances do not contain anything related to the information or ideas that the speaker wants to convey, but clarify the relationship between the speaker and the person who conveys it. The aim of this research is to find out words in the phatic category in comments on Gerindra party social media. The research method used is qualitative descriptive research. The data collection techniques used in this research were observation, note taking and documentation methods. The results of the research show that there is a lot of use of words in the phatic category on the Gerindra party's social media accounts which functions as an emphasis, to start or end a conversation, to refine an order, to ask for approval, as an affirmer.